A planar microstrip coupler with enhanced power coupling - Tan, B; Yassin, G (Institution of Engineering and Technology, 2016)
In this Letter, we present the design of a planar microstrip coupler where power coupling between two parallel microstrip lines can easily be controlled. Enhancement of power coupling is done via two small slots in the ground plane underneath the microstrip pair. The ground plane slots force the field lines near the edge of each microstrip to cross to the adjacent microstrip. The magnitude of the power coupling can easily be controlled by adjusting the length of the slots. Here, we describe the operation of a microstrip coupler, and present the design of a1 X 4 power distributor array that can be used to distribute the input microwave power uniformly to four branch lines arranged in a row. We also present the measured responses of the array, and show that the performance agree very well with simulated results.